Dry Eye Evaluation after Transepithelial Photorefractive Keratectomy - درويش, تيم; يوسف, حبيب; حسن, هبه (Latakia University Journal -Medical Sciences Series, 2020)
Purpose: To evaluate dry eye after transepithelial photorefractive keratectomy (tPRK). Methods: In this prospective study 100 eyes of 50 myopic patients with or without astigmatism underwent transepithelial photorefractive keratectomy, in the ophthalmology department in Tishreen university hospital. A complete ophthalmic evaluation including (OSDI) Ocular Surface Disease Index, (TBUT) Tear Film Break-Up Time and schirmer 1 test were performed preoperatively and at 1, 3 and 6 months after the surgery. Results: Dry eye symptoms increased significantly (P< 0.05) after tPRK at the first and third months after surgery the increase in OSDI values reached about 32.8% and 29.4% respectively, then it decreased to approximately preoperative values (P> 0.05) at the sixth month and the increase in OSDI values was only 10.9%. There was a statistically significant decrease in the result of schirmer 1 test at the first month after tPRK (its values decreased about 11.9%) (P< 0.05), then it returned to approximately preoperative values at the sixth month (the decrease was only about 1.3% and it's statistically insignificant (P> 0.05)). Tear film break-up time decreased after the surgery and it was statistically significant (P< 0.05) at the first and the third month (it decreased about 41% and 34.3%, respectively) but returned to approximately its preoperative values at the sixth month (the decrease was about 12.7% and it's statistically insignificant (P> 0.05)). Conclusion: we can conclude that post tPRK dry eye in low to moderate myopic patients is a transient complication, because although TBUT values decrease and dry eye symptoms increase during the first three months after the surgery and schirmer test values decrease during the first month, they returned to preoperative values after 6 months.